Simulation analysis of the effect of trunk undulation on swimming performance in underwater dolphin kick of human - Nakashima, M. (Journal of Biomechanical Science and Engineering, 2009)
The objectives of this study were to investigate the effect of trunk undulation on the swimming performance in underwater dolphin kick, and to clarify the ideal trunk undulation form. The reference swimming motion of an elite swimmer was firstly acquired from the video analysis, and input into the swimming human simulation model SWUM, which had been developed by the authors. The trunk motion was next optimized by the simulation for three objective functions: maximizing swimming speed, maximizing propulsive efficiency, and minimizing fluid force acting on hands. The following findings were obtained: In the case of maximizing swimming speed, the whole body forms a `C` shape due to the in-phase trunk undulation. The swimming motion of maximizing propulsive efficiency and the reference swimming are considerably similar to each other. In both cases, the trunk moves as a seesaw with a node; whereas, the lower limbs form a traveling wave in the absolute space. The values of propulsive efficiency are around 0.2 in the cases of maximizing propulsive efficiency, minimizing fluid force on hands, and the reference swimming. The swimming motion in the case of minimizing fluid force on hands is almost the same as that of maximizing propulsive efficiency. The trunk undulation with the appropriate amplitudes and phases, especially bending at the chest, is important in realizing the swimming motion which maximizes propulsive efficiency.